Studi Kepustakaan Tersistem Desain Ruang Gender pada Masjid Berdasarkan Mazhab Utama dalam Islam - Azzah Juharida; Noor Cholis Idham; Nensi Golda Yuli (Universitas Sebelas Maret Surakarta, 2023)
This research analyzes and explores theories from various references regarding the design of gender spaces in mosques based on Islam's primary schools of thought. The literature review method in this research uses the Publish or Perish and Google Scholar with the keyword